Distributary behavior of biphasic flows with wood load on an experimental alluvial fan - N. Santibañez; B. Mazzorana; P. Iribarren; L. Mao; I. Rojas (Ingeniería del Agua)
Alluvial fans are episodically affected by the distributary dynamics caused by extreme biphasic flow processes. The solid-fraction component of biphasic flows is generally represented by inorganic sediment, but these events may also carry significant amounts of large wood. The aim of the study was to assess on a physical alluvial fan model the randomness of morphodynamical processes and exposure associated to a set of specific loading conditions and at exploring how these patterns change if large wood is added to the biphasic mixture in a fixed proportion of the solid fraction. The experiments were conducted varying systematically the total volume, the sediment fraction of the biphasic mixture and the applied stream power. Two sets of experiments were run, either with and without a fixed proportion of the solid fraction constituted by large wood. Our results confirm that the exposure associated to specific loading conditions exhibits a remarkable randomness, that the applied stream power has a decisive effect on the variability of exposure and that the fixed portion of large wood strongly interfere with the distributary dynamics on alluvial fans.